Bioactivity of Endophytic Fungi Isolates from Syzygium malaccense Twigs - Hapida, Yustina; Widjajanti, Hary; Salni; Habisukan, Ummi Hiras; Alfarado, Daniel; Elfita (Science and Technology Indonesia, 2024)
Searching for medicinal raw materials derived from the isolation of secondary metabolite compounds is still being carried out to cure a range of illnesses, including infections and degenerative diseases caused by bacteria and free radicals. This research used endophytic fungi extract from the twig of Syzygium malaccense. The diffusion method was used for antibacterial activity and 2,2-diphenyl-1-picrylhydrazyl (DPPH) was used for antioxidant activity. Chemical compound was identified by using NMR spectroscopic method. This research found 5 isolate of endophytic fungi from twig of S. malaccense (YR1 – YR5). Strong antibacterial and antioxidant activity were showed by YR5. Based on molecular identification, YR5 was Fusarium verticillioides. Pure compound prodeced by endophytic fungi F. verticilloides was naphthalene (3-methoxy-7 methylnaphthalene-1,6-diol). This finding can be used as a basis for drug development.